Retention and loss pathways of soluble nutrients in biochar-treated slope land soil based on a rainfall simulator - Selly Maisyarah; Jyun-Yuan Chen; Zeng-Yei Hseu; Shih-Hao Jien (Elsevier, 2023)
Global food crisis makes intense agricultural activity necessary, which accelerates soil degradation and increases pollution risk to nearby catchments. Application of biochar can effectively retain plant-required nutrients in soils. However, the linkage between retention and loss pathways of nutrients is still unclear, particularly at slope lands. Therefore, a simulated rainfall experiment (rainfall intensity ​= ​50 ​mm ​h−1) was conducted in a sandy soil with 10° gradient slope (indoor experiment) to clarify loss pathways of soluble C, N, P and K in biochar-amended soils. Wood biochar pyrolized at 300 ​°C (LWB) or 600 ​°C (HWB) was applied at 1% (LWB1; HWB1) or 2% (LWB2; HWB2). Our results show that the pathways for C, N, P and K loss was percolation ​> ​surface runoff ​> ​soil erosion. Compared to control, HWB2 treatment had a 2-4 times higher infiltration amount but 5-6 times lower surface runoff and soil loss, indicating that this treatment alleviated nutrient loss via erosion and runoff in the sloped soil. Among all treatments, HWB2 treatment was the most effective for retaining organic C, dissolved organic C, total N, and exchangeable K through various pathways. However, a substantial amount of soluble P was lost through percolation. Therefore, the potential pollution of groundwater by P through percolation pathway should be considered during biochar application.